Exploring the Transformative Potential of Practice-based Design Research (PBDR) Methods in Architectural Design Pedagogy - Felix, Sandra (Arts Research Africa, 2022)
This paper discusses the application of practice-based design research (PbDR) methods in transforming the design practice of architecture students. It explores how reflection and diffraction, two PbDR methods, can be used to shape students’ design practice and challenge institutional biases. The author shares the experience of implementing these methods in a third-year architecture design studio at the University of the Witwatersrand in South Africa. Changes were made to the curriculum, including the introduction of reflection and the use of diffractive methods, to foster personal and institutional transformation. The paper highlights the importance of collaborative dialogue, social reflection, and engaged pedagogy in this transformative process.